«Ալեքսանդրի Վեպի» հին հայերեն թարգմանության բնագիրը և ազդեցությունը հայ միջնադարյան գրականության վրա - Թոփչյան, Արամ
The article briefly discusses four old Armenian recensions of the Alexander Romance in comparison with those of the original Greek text. Three of the Arme-nian recensions (Ա [A], Բ [B] and Գ [C]) have been included in the “diplomatic” edition prepared by Hasmik Simonyan, who has erroneaously regarded recension B (instead of A) as the oldest Armenian witness. The fourth, short recension, which may be of interest with regard to the textual tradition of the work, has not been punlished yet and is currently prepared for publication by the author. As for the possible fifth, “intermediary” recension, it still remains somewhat obscure and needs further study. В статье кратко охарактеризованы четыре древнеармянские редакции Романа об Александре в сопоставлении с редакциями греческого оригинала. Три из армянских редакций (Ա [A], Բ [B] и Գ [C]) были включены в “дипломатическое” издание, подготовленное Асмик Симонян, которая ошибочно считала редакцию В (а не A) самой ранней. Четвертая, краткая редакция, которая может быть интересна с точки зрения текстуальной традиции памятника, впервые готовится к изданию автором настоящей статьи. Что касается возможной пятой, «промежуточной» редакции, вопрос о ее существовании нуждается в исследовании.
Keywords: Ձեռագրեր; Թարգմանություն; Միջնադարյան գրականություն